TINGKAT MINAT PETERNAK SAPI POTONG DALAM PENERAPAN TEKNOLOGI INSEMINASI BUATAN DI KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO (Level of Interest of Beef Cattle Farmers in the Application of Artificial Insemination in Asembagus District, Situbondo Regency) - Ali, Isbat; Sumardani, Ni Luh Gde; Tatik Inggriati, Ni Wayan (Universitas Nusa Cendana, 2025)
Breeders interest influences the adoption rate of artificial insemination. This research aims to determine the factors related to the level of interest of breeders in implementing artificial insemination (AI) technology to increase the beef cattle population in Asembagus District, Situbondo Regency. This research was conducted using a survei method with a total of 96 farmer respondents. The data sources used are primary and secondary data. Data was collected through observation, in-depth interviews with the help of questionnaires. The analysis used was, 1) test the validity and reliability test of the questionnaire’s feasibility, 2) test the analysis prerequisites to the determine the parametric and non-parametric statistical values of the questionnaire data, and 3) multiple linear regression containing the T test, F test, R (correlation coefficient) and r2 (coefficient of determination) was to determine the effect of the independent variable on the dependent variable. The results of the three data analyses show that non-formal education has the lowest positive influence (11.94%), farming experience has a negative influence (14.61%), community environment has a positive influence (18.32%), and age has the largest positive influence (19.55%). Older breeders have a deeper understanding and experience regarding AI. The conclusion of this research was that the age of the farmer influences the level of interest of beef cattle breeders in Asembagus district Situbondo regency in implementing AI technology.